Rancangan Aplikasi Presensi Kehadiran Mahasiswa Program Studi Sistem Informasi Universitas Tama Jagakarsa Secara Online Berbasis Android - Tiyas Rosaidi Anwar (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Presence attendance is a data collection activity to determine the number of attendance at an event or activity. Any activity that requires information about participants will certainly carry out the presence process. This also happens in the learning process. With the application of the results of this thesis, it is hoped that it will make it easier for students to carry out attendance and also make it easier for lecturers to obtain student attendance data. The process of filling in attendance using this application is very easy and does not require a long time, unlike using sheets of paper where students have to take turns filling in attendance data. It is also hoped that this system will continue to be used when lecture activities are carried out online or when lectures are carried out normally in class. This research took place at TAMA Jagakarsa University and the data used in this study are primary data and secondary data. Making the application in this thesis begins with analyzing requirements, creating a system design, making a system display design, coding or making an application in codular, then do black box testing. Keywords: Online Presence Information System, Android application, Information Systems Study Program at TAMA Jagakarsa University.